ECRANISATION OF INTRINSIC ELEMENTS IN THE NOVEL AND FILM CINTA DALAM IKHLAS - Muhammad Danial; Rezky Khoirina Tarihoran; Ayu Melati Ningsih; Diana Sopha (Journal of Language and Literature, 2026)
This study aims to describe the ecranisation process of intrinsic elements, including plot, characters, and settings, from the novel "Cinta dalam Ikhlas" (2017) by Kang Abay into its film adaptation (2024) directed by Fajar Bustomi. The method employed is descriptive qualitative with content analysis techniques. The ecranisation theory used covers three main processes: reduction (shrinkage), expansion (addition), and variation change. The results show that in the plot aspect, there is a reduction in the main character's middle school memories and a variation change in the exam announcement medium from newspapers to online systems. In the character aspect, there is a reduction in the number of the main character's siblings and the removal of several supporting characters. Meanwhile, in the setting aspect, visual adjustments were made to support the dramatization of the story on the big screen. In conclusion, the transformation from novel to film underwent various significant changes to adapt to the duration and aesthetics of audio-visual media without losing the essence of the religious message in the story.